Enforcement of Sharia Bank Employee Integrity through the Application of Islamic Ethics in the Principles of Good Corporate Governance - Agus Prakarsa Yuristama; Neneng Nurhasanah; Udin Saripudin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The world of banking is an activity based on the principle of trust. The public will place their funds in a bank that is considered trustworthy. Humans are creatures who are blessed with lust and Bank employees are humans. In addition, humans are also not free from sin and mistakes. In this case, there is an issue of human weakness as an employee of the Bank, but the Bank is an institution that is trusted by customers. As with other life problems, the definite solution is the values of religious norms which are expected to give rise to ethical values from banking employees in carrying out their roles as part of public trust institutions. The actual ethics that have developed in the banking world, including Indonesian banking, are through good governance. In this article, we will try to discuss how an ethical value of Islamic economics characterizes the principles of good governance and how good governance can strengthen the integrity of Islamic banking employees in Indonesia. This article was created using a qualitative research approach or method with a case study model. This study can conclude that the concept of Islamic economic ethics has given color to the principles of Good Corporate Governance as applied to Indonesian Islamic banking.